Gene duplication at the achaete-scute complex and morphological complexity of the peripheral nervous system in Diptera. - Skaer, N.; Pistillo, D.; Gibert, J.M.; Lio, P.; Wulbeck, C.; Simpson, P. (Trends in Genetics, 2002)
The number of achaete-scute genes increased during insect evolution, particularly in the Diptera lineage. Sequence comparison indicates that the four achaete-scute genes of Drosophila result from three independent duplication events. After duplication, the new genes acquired individual expression patterns but, in Drosophila, their products can compensate for one another, which raises the question: why retain all four genes? The complexity of the spatial expression of these genes on the notum increased in the lineage leading to the higher Diptera, allowing the development of stereotyped bristle patterns. This probably coincided in time with gene duplication events, raising the possibility that an increase in gene copy number might have provided the flexibility necessary for more complex transcriptional regulation.